The Palestinian refugee question: root causes and breaking the impasse - Albanese, F; Lilly, D (Refugee Studies Centre, University of Oxford, 2019)
Acknowledging the root causes of Palestinian displacement and objectively applying international law will be key to any solution to the Palestinian refugee question. Recent attempts to dismiss the Palestinian refugee issue altogether make this all the more imperative.